Immunotherapy-induced severe neutropenia with neurotoxicity: A case of a 75-year-old woman with ulcerative colitis diagnosed with melanoma. (April 2020) - Patel, Rima; Pai, Lori
Introduction: Immune checkpoint inhibitors have transformed the field of oncology moving immuno-oncology to the forefront of cancer treatment. However, immune checkpoint inhibitors can result in serious immune-related adverse events. Hematologic toxicities are rare with incidence of neutropenia from nivolumab less than 1%. Case report: We present a case of refractory neutropenia in a 75-year-old woman with ulcerative colitis on adjuvant nivolumab for stage III melanoma. Management and outcome: The patient's neutropenia did not improve with high-dose intravenous steroids, filgrastim, mycophenolate mofetil, or intravenous immunoglobulin. She also developed significant neurological symptoms from nivolumab. She was transitioned to comfort measures given her persistent symptoms and poor functional status. Discussion: Though hematologic malignancies of immune checkpoint inhibitors are rare, they should be considered after other diagnoses are excluded. We discuss the serious immune-related adverse effects of immune checkpoint inhibitors in a patient with an underlying autoimmune disease and general treatment approaches.